Mechanical Characteristics and Mesostructural Damage of Saturated Limestone under Different Load and Unload Paths - Jielin Li; Liu Hong; Keping Zhou; Caichu Xia; Longyin Zhu (Advances in Civil Engineering)
To study the evolutionary characteristics of mesostructural damage to saturated limestone under different loading and unloading paths, three types of loading and unloading tests involving three different loading rates and initial peak stresses were performed. Nuclear magnetic resonance technology and scanning electron microscopy were used to investigate the evolutionary characteristics of pore water during the loading and unloading of the limestone. The results indicated that, with an increase in the initial peak stress, the rock viscoplasticity gradually decreased, and the variation of pore radius and the reduction of bound water decreased. With an increasing loading rate, the mesostructure evolution law under disturbance-increasing amplitude (DIA) cycling was opposite to those under increasing amplitude (IA) and repeated-increasing amplitude (RIA) cycling. With the increasing loading stress level, the porosity decreased and then increased. Under increasing amplitude cycling, a larger initial porosity resulted in higher pore compaction and expansion limits. Reducing the initial peak stress inhibited the pore expansion, whereas it had the opposite effect under RIA and DIA cycling. During loading and unloading, bound water exists in pores of organic matter and mesopores, and free water exists in macropores of intergranular and transgranular fractures. These changes indicate certain laws under different loading and unloading paths. The results of this study indicate that the mesostructure characteristics of rock depend on the loading and unloading paths.